2007
DOI: 10.1111/j.1460-9568.2007.05604.x
|View full text |Cite
|
Sign up to set email alerts
|

Disgust sensitivity predicts the insula and pallidal response to pictures of disgusting foods

Abstract: The anterior insula has been implicated in coding disgust from facial, pictorial and olfactory cues, and in the experience of this emotion. Personality research has shown considerable variation in individuals' trait propensity to experience disgust ('disgust sensitivity'). Our study explored the neural expression of this trait, and demonstrates that individual variation in disgust sensitivity is significantly correlated with participants' ventroanterior insular response to viewing pictures of disgusting, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 55 publications
10
104
4
Order By: Relevance
“…In other words, the neural circuitry underlying the pro- cessing of angry expressions is only fully realized by taking variation in relevant emotional dimensions into consideration. This accords with other recent research emphasizing the importance of individual differences to neural responses to food stimuli (Beaver et al, 2006;Calder et al, 2007) or happy and fearful facial expressions (Canli et al, 2002;Bishop et al, 2004).…”
Section: Bis and Dorsal Anterior Cingulatesupporting
confidence: 76%
“…In other words, the neural circuitry underlying the pro- cessing of angry expressions is only fully realized by taking variation in relevant emotional dimensions into consideration. This accords with other recent research emphasizing the importance of individual differences to neural responses to food stimuli (Beaver et al, 2006;Calder et al, 2007) or happy and fearful facial expressions (Canli et al, 2002;Bishop et al, 2004).…”
Section: Bis and Dorsal Anterior Cingulatesupporting
confidence: 76%
“…40,42 Research increasingly implicates the orbitofrontal cortex and the anterior insula in disgust-related processes, [43][44][45][46] in contrast to the well-observed pattern of amygdala activation during the processing of fear. 42 For instance, studies specifically demonstrate that disgust facial expressions activate the anterior insula 44,[47][48][49] relative to neutral and fear facial expressions. Further, normalization in the activity of the insula, prefrontal cortex, orbitofrontal cortex, and other neighbouring regions has been noted to occur following CBT and pharmacological treatments for OCD, [50][51][52] suggesting the potential for improvement in disgust recognition following successful treatment.…”
Section: Limitationsmentioning
confidence: 99%
“…Today, a number of reports are to be found within the fMRI literature in which disgust experiences are indeed described as being associated with insula activation (e.g. Wicker et al, 2003;Schienle et al, 2002;Schäfer et al, 2005;Fitzgerald et al, 2004;Wright et al, 2004;Shapira et al, 2003;Phillips et al, 1998Phillips et al, , 2000Stark et al, 2007;Calder et al, 2007). The paradigms adopted involve external (e.g., visual, auditory, olfactory) or internal (imagery) disgust-induction methods.…”
Section: Fmri Research On Emotion Specificitymentioning
confidence: 95%
“…With regard to disgust states and disgust traits, the results are however inconsistent. While some research groups have observed positive correlations between insula activation and both self-reports of experienced disgust and trait disgust (Calder et al, 2007;Mataix-Cols et al, 2008), others have found a positive relationship between disgust sensitivity and activation of both the amygdala Stark et al, 2005b) and the pallidum (Calder et al, 2007;Mataix-Cols et al, 2008).…”
Section: Fmri Research On Emotion Specificitymentioning
confidence: 96%
See 1 more Smart Citation